Prevalence of respiratory viruses among children hospitalized from respiratory infections in Shenzhen, China. Issue 1 (December 2016) - Wang, Heping; Zheng, Yuejie; Deng, Jikui; Wang, Wenjian; Liu, Ping; Yang, Fanghua; Jiang, Hanfang
Abstract Background The prevalence of local dominant viral etiologies is important for clinical management and prevention of common viral respiratory tract infections. Unfortunately, there is limited large-scale data about common viral respiratory infection in south China. To survey dominant viral etiology and seasonality of acute respiratory infections in hospitalized children, a 4-year consecutive study was conducted in Shenzhen, China. Methods Nasopharyngeal swab specimens were obtained from 30, 443 hospitalized children younger than 14 years with respiratory tract diseases in Shenzhen Children's Hospital from January 2012 to December 2015. Nasopharyngeal swabs were routinely examined by direct immunofluorescence assay to detect respiratory agents including seven respiratory viruses. Data were analyzed to describe the frequency and seasonality. Results Of the 30, 443 children enrolled in the study, 4428 (14.55 %) were positive for at least one viral pathogen, among whom 4110 (92.82 %) were ≤3 years of age. The predominant viruses were respiratory syncytial virus (RSV, 68.11 %), adenovirus (ADV, 16.01 %) and parainfluenza virus 3 (PIV-3, 11.0 %). The common respiratory viruses detected peaked in the spring (17.69 %), and were minimal in autumn (9.73 %), but PIVs detection peaked in November. The common virus detection rate in male subjects (15.40 %) was significantly higher than in female subjects (13.02 %). PIVs detection rates were complementary with RSV in autumn in each year. Conclusions This study demonstrated common respiratory viruses were the major cause of hospitalized acute respiratory infection (ARI) in children in Shenzhen, China. RSV was the most common detected infection, while ADV was the predominant pathogen in hospitalized children. These findings provide a better understanding of virus distribution among children of different ages, infection stratification by gender, and seasonality, all of which will contribute to modification of therapeutic approaches and development of effective prevention strategies for each respiratory virus infection during peak seasons.